Angiotensin II type-1 receptor (AT(1)R) regulates expansion, differentiation, and functional capacity of antigen-specific CD8(+) T cells - Silva-Filho, João Luiz (Sci Rep, 2016)
Angiotensin II (Ang II) and its receptor AT(1) (AT(1)R), an important effector axis of renin-angiotensin system (RAS), have been demonstrated to regulate T-cell responses. However, these studies characterized Ang II and AT(1)R effects using pharmacological tools, which do not target only Ang II/AT(1)R axis. The specific role of AT(1)R expressed by antigen-specific CD8(+) T cells is unknown. Then we immunized transgenic mice expressing a T-cell receptor specific for SIINFEKL epitope (OT-I mice) with sporozoites of the rodent malaria parasite Plasmodium berghei expressing the cytotoxic epitope SIINFEKL. Early priming events after immunization were not affected but the expansion and contraction of AT(1)R-deficient (AT(1)R(−/−)) OT-I cells was decreased. Moreover, they seemed more activated, express higher levels of CTLA-4, PD-1, LAG-3, and have decreased functional capacity during the effector phase. Memory AT(1)R(−/−) OT-I cells exhibited higher IL-7Rα expression, activation, and exhaustion phenotypes but less cytotoxic capacity. Importantly, AT(1)R(−/−) OT-I cells show better control of blood parasitemia burden and ameliorate mice survival during lethal disease induced by blood-stage malaria. Our study reveals that AT(1)R in antigen-specific CD8(+) T cells regulates expansion, differentiation, and function during effector and memory phases of the response against Plasmodium, which could apply to different infectious agents.